El proceso de evaluación del talento humano y su incidencia en el desempeño laboral de la empresa Postecon s.a., sucursal Pastocalle, de la ciudad de Latacunga, provincia de Cotopaxi, en el período 2013 - Toctaguano Mendoza, Mariela Celina (2015)
This research was performed by the lack of assessment processes human resources in the "POSTECON SA." company, Which allows to know their employees work performance, the human factor remains the cornerstone development of any business is very important its periodic assessment once the problem was identified proceeded to the information collection and analysis related to the development of human talent within the company applying and explanatory research to assess qualitative and quantitative staff with analytical, deductive methods, and techniques of the survey interview….